Probiotic characteristics and whole-genome sequence analysis of Pediococcus acidilactici isolated from the feces of adult beagles - Zhao, Mengdi; Liu, Keyuan; Zhang, Yuanyuan; Li, Yueyao; Zhou, Ning; Li, Guangyu (Frontiers in Microbiology, 2023)
The beneficial effects of lactic acid bacteria are well known and recognized as functional foods that are health benefits for companion animals. This study, for the first time, reports the probiotic properties, safety and whole-genome sequence of Pediococcus acidilactici GLP06 isolated from faeces of beagles. In this study, candidate probiotic bacteria P. acidilactici GLP02 and GLP06 were morphologically characterized and tested for their antimicrobial capacity, tolerance to different conditions (low pH, bile salts, an artificial gastrointestinal model and high temperature), antibiotic sensitivity, hemolytic activity, cell surface hydrophobicity, autoaggregation activity and adhesion to Caco-2 cells. P. acidilactici GLP06 showed better probiotic potential. Therefore, P. acidilactici GLP06 was evaluated for in vivo safety in mice and whole genome sequencing. The results showed, that the supplemented MG06 group (1010 cfu/mL), GLP06 was not only nontoxic to mice, but also promoted the development of the immune system, improved resistance to oxidative stress, and increased the diversity of intestinal microorganisms and the abundance of Lactobacillus. Whole-genome sequencing showed that P. acidilactici GLP06 was 2,014,515 bp and contained 1,976 coding sequences, accounting for 86.12% of the genome, with no drug resistance genes and eight CRISPR sequences. In conclusion, the newly isolated canine-derived P. acidilactici GLP06 had good probiotic potential, was nontoxic to mice and promoted the development of immune organs, improved the biodiversity of the intestinal flora, and had no risk of drug-resistant gene transfer, indicating that P. acidilactici GLP06 can be used as a potential probiotic for the prevention and treatment of gastrointestinal diseases in companion animals.